Edukasi Budidaya Sayuran dan Bunga Hias Organik pada Yayasan “Cahaya Alam” Desa Kucur Kota Malang - Eny Dyah Yuniwati; Umi Afdah (University of Merdeka Malang, 2021)
Organic farming is a natural cultivation system without using chemicals. These organic vegetables and ornamental flowers are cultivated naturally by compost and using organic pesticides. The fertilizer used in this educational process is compost fermented with Local Micro Organisms or MOL, at the location of the Cahaya Alam Foundation which is located in Kucur Village, Dau District, Malang Regency. The method used is to educate about growing organic vegetables and ornamental flowers properly, with limited land conditions. The solution given was to create an effective planting medium for cultivating organic vegetables and ornamental flowers in accordance with the limited land available at the Cahaya Alam Foundation. The planting medium uses polybags, and a simple screen house for organic vegetable nurseries. The output obtained from organic farming education is to provide assistance in the cultivation of organic vegetables at the demonstration plot, construction of screen houses and simple polybags, providing counseling, mentoring and learning to solve problems in cultivating organic vegetables and ornamental flowers at the Cahaya Alam Foundation.DOI: https://doi.org/10.26905/abdimas.v6i2.5116